The Influence Of World Oil Prices, Inflation, USD/IDR EXCHANGE, And Bi-Rate On Stock Prices: Studi Empiris pada Perusahaan Sektor Kesehatan di Bursa Efek Indonesia Periode Tahun 2018-2022 - Nila Amelia Aji; R. Yuniardi Rusdianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the impact of global and domestic economic factors on the share prices of health sector companies on the Indonesia Stock Exchange from 2018 to 2022. The impact is analyzed simultaneously and partially on 13 of the total 31 health sector companies sampled using linear regression analysis multiple. The data used is secondary data taken from monthly information summaries. The F Test results show that world oil prices, inflation, the USD/IDR exchange rate, and the BI-Rate together have a significant effect on the share prices of health sector companies on the Indonesia Stock Exchange. However, from the T Test results, only world oil prices have a positive and significant influence on stock prices. Meanwhile, inflation, the USD/IDR exchange rate, and the BI-Rate do not have a significant influence on the share prices of health sector companies. These variables overall influence the stock prices of health sector companies by 49.7%, while 50.3% are influenced by other factors not investigated in this study.